¿Es aspectual o temporal el carácter de la oposición imperfectivo /perfectivo? - Pawlak, Aneta (Studia Romanica Posnaniensia, 2007)
In this article, we present a short historical summary of the following terms: the aspect and the imperfective /perfective opposition to answer the question if the imperfective /perfective opposition has an aspectual or temporal character. We distinguish two types of the aforementioned opposition: the temporal imperfective /perfective opposition expressed by the Spanish tenses Pretérito Indefinido / Pretérito Imperfecto that is characterized by the property of [± temporal delimitation]; and the aspectual imperfective /perfective opposition recognizable in the aspectual system of the Slavonic languages that is characterized by the property of [± conclusion of the process].